Volume 5: Turbo Expo 2002, Parts a and B 2002
DOI: 10.1115/gt2002-30340
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Secondary Air Injection on the Performance of a Transonic Turbine Stage

Abstract: This paper presents results of rig testing of a transonic, single stage turbine with various modifications made to the injection of secondary air into the mainstream. Results show that significant improvements in stage efficiency can be realized by optimizing the injection of upstream disk purge and rotor upstream shroud leakage flow into the mainstream flow. Results of CFD simulations of the rotor upstream disk purge flow test conditions and closely simulated test geometry agree well with test data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…By means of this loss breakdown method, the space location has distinguished viscous shear loss and blockage effects described before, and the proportion of the three losses for IR ¼ 0.9% is 61.09% for the viscous shear loss, 19.05% for the vortex interaction between the rotor hub passage vortex and egress flow, and 19.86% for the blockage effect. This proportion agrees well with the results that the viscous shear gives rise to more than half the total losses, 9,12 while the loss from the vortex interaction is close to that from the blockage effect. 12 The losses caused by the blockage effect for the stator and rotor under different rim seal flow rates are listed in Table 4.…”
Section: Loss Mechanismssupporting
confidence: 91%
See 1 more Smart Citation
“…By means of this loss breakdown method, the space location has distinguished viscous shear loss and blockage effects described before, and the proportion of the three losses for IR ¼ 0.9% is 61.09% for the viscous shear loss, 19.05% for the vortex interaction between the rotor hub passage vortex and egress flow, and 19.86% for the blockage effect. This proportion agrees well with the results that the viscous shear gives rise to more than half the total losses, 9,12 while the loss from the vortex interaction is close to that from the blockage effect. 12 The losses caused by the blockage effect for the stator and rotor under different rim seal flow rates are listed in Table 4.…”
Section: Loss Mechanismssupporting
confidence: 91%
“…However, the influence of the rim seal flow on the mainstream involves complex factors, such as rim seal flow blockage, viscous shear between the rim seal flow and mainstream and vortex interaction between the rim seal flow and hub passage vortex. [9][10] Among these factors, the blockage effect resulting from the rim seal flow is one of the most significant flow phenomena and has not been investigated in detail. Schuepbach et al 11 found that the pressure in front of the ejection increased as a consequence of the introduced blockage when the ejection left the rim seal with the experimental and computational method.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the total anergy produced along the domain increases with an increased purge flow rate (see Fig. 15 c) which is compliant with studies dealing with the influence of purge flow rate on the losses generated in turbines [11,31,33] .…”
Section: Influence Of Purge Flow Rate On Viscous Anergy Productionsupporting
confidence: 84%